PENGARUH INFLASI TERHADAP KESTABILAN DAN EKSISTENSI USAHA EKONOMI MIKRO - Erik Bisri Alamsyah; Kushartono Kushartono; Yoan Catur Arinsa (Yos Soedarso Economic Journal (YEJ), 2021)
Indonesia, as a developing country, realizes the importance of economic development to create national welfare. This national development covers various aspects of life such as the political, social, cultural, economic and defense and security sectors aimed at meeting the needs of all Indonesian people, whose main objective is towards a just and prosperous Indonesian society.Economic growth is a measure for the success of a country's development, especially in the economic field. A country has an economic growth that has increased continuously every year will promote development in that country. In macroeconomics, the overall economic condition of a country is explained in relation to economic growth. The success of a country's development lies in its economic growth. Therefore, the ups and downs of the economy will certainly affect several sectors.In the economy of a country or a region, in fact there are various sectors that show the level of economic growth, namely the formal and informal sectors. In the informal sector, generally small businesses with limited capital, scope and development and received very little official protection from the government. There are also many informal sectors that can be appointed as an activity or job to generate income in a community, one of which is establishing their own business or by establishing micro, small and medium enterprises (MSMEs). Micro, Small and Medium Enterprises are the business groups that have the largest number. The micro, small and medium enterprises are regulated based on Law Number 20 of 2008 concerning UMKM Article 1 number 1 what is meant by Micro Enterprises are productive businesses owned by individuals or individuals and / or individual business entities.2 Micro Economic Businesses are businesses that have the potential to be affected by the impact of there is an economic phenomenon, namely inflation.Keywords: UMKM; National development; National Economy.